The role of extracellular polymeric substances on the sorption of pentachlorophenol onto natural biofilms in different incubation times: a fluorescence study. Issue 2 (7th February 2017) - Dong, Deming; Zhang, Liwen; Guo, Zhiyong; Hua, Xiuyi
ABSTRACT: Extracellular polymeric substances (EPS) have been regarded as the most significant components in sorbing organic contaminants onto natural biofilms. However, few investigations have reported the effects of EPS on the sorption of organic contaminants onto biofilms in different incubation times. Here, pentachlorophenol (PCP), selected as a model organic pollutant, was sorbed by biofilms and EPS-free biofilms cultured for 15, 30, and 45 days, to evaluate the role of EPS in the sorption process. EPS were extracted from biofilms to investigate the binding mechanism of PCP to the fluorescence matters in EPS by fluorescence quenching titration. Results showed that EPS, bound with biofilms or released to water, could increase or decrease the sorption amounts of PCP on biofilms in various incubation times. The presence of bound EPS in biofilms enhanced the sorption amounts of 30-day biofilms (6.0 ± 0.11 μmol g −1 ) because of the formation of the EPS-PCP complex between PCP and fluorescence matters in EPS, such as protein-like matters. In contrast, the release of PCP-bound EPS in 15- and 45-day biofilms decreased the sorption amounts of PCP on biofilms. All the results suggested that EPS dominated the sorption of PCP onto biofilms.